2003
DOI: 10.1088/0029-5515/43/9/324
|View full text |Cite
|
Sign up to set email alerts
|

Predictive study of high performance scenarios in HL-2A

Abstract: High performance scenarios in the HL-2A tokamak are studied by numerical modelling. Through shifting the plasma column outwards, a shaped plasma with significant triangularity is achieved with sufficient room left for the RF antenna. For the out-shifted, shaped plasma, ripple loss of high energy ions during neutral beam injection (NBI) is analysed, and the results show that the ripple loss fraction of NBI power for the shaped plasma is no higher than that for the unshifted circular plasma. The time dependent T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Here, β N = β T /(I /aB T ) is the normalized toroidal β, β T = 2µ 0 p /B 2 T , I is the plasma current in MA, a is the plasma minor radius in m, B T is the toroidal magnetic field in Tesla; H 89 is the confinement enhanced factor relative to ITER89-P scaling [9]. The DB plasma is then a promising regime for high performance steady operation [3,4,10,11]. However, the transport barriers lead to large pressure gradient P and large bootstrap current density J BS , which often drive MHD instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Here, β N = β T /(I /aB T ) is the normalized toroidal β, β T = 2µ 0 p /B 2 T , I is the plasma current in MA, a is the plasma minor radius in m, B T is the toroidal magnetic field in Tesla; H 89 is the confinement enhanced factor relative to ITER89-P scaling [9]. The DB plasma is then a promising regime for high performance steady operation [3,4,10,11]. However, the transport barriers lead to large pressure gradient P and large bootstrap current density J BS , which often drive MHD instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…where n ||0 and R 0 refer to the toroidal mode number n launched at the antenna R 0 , q2 = q cyl /εx (q cyl is the cylindrical safety factor, ε = a/R) is a magnetic geometry factor, and ε ⊥ = 1 + ω 2 pe /ω 2 ce -Σ j ω 2 pi,j /ω 2 (ω ce , ω pi and ω pe are the electron gyro-frequency, ion and electron plasma frequencies, respectively) [27] . So the safety factor and density can affect the absorption of the LHW power.…”
Section: Discussionmentioning
confidence: 99%
“…5a). The analysis of wave deposition region in the ( , n // ) phase space shows that constraint imposed by the wave propagation condition limits the maximum allowed n // -upshift [17]. Taking into account the Landau damping condition, it is shown that LH power deposits off-axis.…”
Section: Lower Hybrid Wave Heating and Eitbmentioning
confidence: 99%